(untitled) ("Journal "U". Economy. Management. Finance.", 2018)
This article examines the system of relationships between subjects of the banking sector, which have certain characteristics and problems. The author characterizes the qualitative system of selling services by commercial banks, which allows to combine the quality vision both from the side of the bank and from the client’s side. The relevance of the article is primarily due to the fact that in a modern market the bank and the client are primarily partners, and this has a significant impact on the process of selling banking services.